A systematic review on identifying factors influencing total quality management implementation - Al Aliyani, Wafa Rashid; Lee, Chia Kuang (IPS, 2022)
In the era of globalization and advanced international trade, the importance of using total quality management (TQM) in the manufacturing companies is growing rapidly. This paper systematically reviews previous literature on the factors influencing total quality management implementation. While introducing TQM, previous studies have measured critical success factors. A systematic review of previous literature was performed from 2007-2020 and the analysis of 153 studies revealed that there are 10 key dimensions of TQM that are widely used as a measurement. Our examination shows that, despite having a shared relationship with its customers and "consumer attention/satisfaction" being unmistakably recognized as one of the major CSFs of TQM. The linkages between TQM Critical success factors, TQM and leadership and promotion, have received minimal research so far. People are the most important emphasis of business, even though consumer happiness may be thought of as the Quality management philosophy's main goal. Positive results are anticipated when cultures and quality management systems attempted to demonstrate are taken into account together. TQM literature from the past has noted that systemic behavior results either via the creation of an attitude or through the primary aspect of the quality management system. Businesses invest in cultural and structural resources to provide the right environment for TQM.